Contract Farming of Potato in Punjab: A Comparative Study (Indian Journal of Extension Education, 2021)
The present study was conducted in Hoshiarpur district in Punjab during year 2019-2020. Data were collected from 98 respondents who were practicing contract farming and non-contract farming of potato. The study revealed that all the contract farmer respondents had purchased their seeds from the contracting agency while the majority of non-contract respondents purchased their seeds privately which was significantly different. All the contract respondents had used FC 3 (FL1867) variety whereas 77.55 per cent of non-contract respondents used the Kufri Pukhraj variety (an early sown variety). All the contract respondents followed more than recommended row to row-R spacing whereas the majority of non-contract respondents followed the recommended spacing which shows that data was varying significantly. In contract respondents, the majority had harvested their crop in 70-80 days whereas 71.49 per cent of non-contract respondents harvested their crop in 60-70 days. Majority of contract and non-contract respondents got a yield of about 90-120 q/acre.